ChemInform Abstract: An Unprecedented Pd‐Catalyzed trans‐Addition of Boronic Acids to Ynamides. Issue 24 (2nd June 2014) - Yang, Yuanfa; Wang, Lina; Zhang, Jieni; Jin, Yali; Zhu, Gangguo
Abstract The title reaction affords α, β‐disubstituted enamides such as (III), (V), and (VII) in good yields with high regio‐ and stereoselectivity.